Power Quality Enhancement inMulti-level Inverter for PV Based Grid-Connected System Utilizing Modified MPPT (International Journal of Food and Nutritional Sciences, 2022)
Energy experts are designing an optimal grid to meet the rising demand for green and sustainable power. Solar electricity may be more efficiently added to the electrical grid by using Grid-Connected System (GCPS). However, power quality needs issues to be addressed. Among the latest developments in solar energy technology are multi-level inverters in order to employParticle Swarm Optimization (PSO) based MPPT direct predictive control for the output. This paper uses MATLAB Simulink to design and study the use of H-bridge multilevel inverters in grid-connected solar systems. In order to fine-tune the existing direct model predictive control strategy, this researchis adding amodified MPPT algorithm.Results validate both the voltage and current THD of 9 levels ideally followed by IEEE standards. This paper enhances the existing approach by PSO, which leads to lower levels of THD in both the current and the voltage.